Two-dimensional infrared correlation spectroscopy, conductor-like screening model for real solvents, and density functional theory study on the adsorption mechanism of polyvinylpolypyrrolidone for effective phenol removal in an aqueous medium - Mohammad Alwi, M.A.; Normaya, E.; Ismail, H.; Iqbal, A. K. M. A.; Mat Piah, B.; Abu Samah, M.A.; Ahmad, M.N. (American Chemical Society, 2021)
The discharge of industrial effluents, such as phenol, into aquatic and soil environments is a global problem due to its serious negative impacts on human health and aquatic ecosystems. In this study, the ability of polyvinylpolypyrrolidone (PVPP) to remove phenol from an aqueous medium was investigated. The results showed that a significant proportion of phenol (up to 74.91%) was removed using PVPP at pH 6.5. Isotherm adsorption experiments of phenol on PVPP indicated that the best-fit adsorption was obtained using Langmuir models. The response peaks of the hydroxyl groups of phenol (OH) and the carboxyl groups (i.e., C=O) of PVPP were altered, indicating the formation of a hydrogen bond between the PVPP and phenol during phenol removal, as characterized using 1D and 2D IR spectroscopy. The resulting complexes were successfully characterized based on their thermodynamic properties, Mulliken charge, and electronic transition using the DFT approach. To clarify the types of interactions taking place in the complex systems, quantum theory of atoms in molecules (QTAIM) analysis, reduced density gradient noncovalent interaction (RDG-NCI) approach, and conductor-like screening model for real solvents (COSMO-RS) approach were also successfully calculated. The results showed that the interactions that occurred in the process of removing phenol by PVPP were through hydrogen bonding (based on RDG-NCI and COSMO-RS), which was identified as an intermediate type (∇2ρ(r) > 0 and H < 0, QTAIM). To gain a deeper understanding of how these interactions occurred, further characterization was performed based on adsorption mechanisms using molecular electrostatic potential, global reactivity, and local reactivity descriptors. The results showed that during hydrogen bond formation, PVPP acts as a nucleophile, whereas phenol acts as an electrophile and the O9 atom (i.e., donor electron) reacts with the H22 atom (i.e., acceptor electron).